English Learning Achievement Through the Application of Cooperative Integrated Reading and Composition (Circ) Learning Model With Audio-V Media - Amrina, Hafidza Nash'ul; Setianingsih, Tri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This class action research was conducted in junior high school with the aim to improve English learning achievement of students of class VIII A SMP Negeri 1 Sumberrejo through the application of Cooperative Integrated Reading and Composition (CIRC) learning model with Audio-V media. The subjects of this study were 34 students of class VIII A SMP Negeri 1 Sumberrejo in English subject. Data on students' learning achievement was obtained by using the test method with the instrument in the form of a learning achievement test. The data was then analyzed using quantitative descriptive analysis techniques. The result of this study is the application of Cooperative Integrated Reading and Composition (CIRC) learning model with Audio-V media can improve the English learning achievement of students of class VIII A SMP Negeri 1 Sumberrejo in the first semester of the 2024/2025 academic year. The average score of students' learning achievement showed an increase from cycle I to cycle II. The class average of learning achievement at the beginning of learning only reached 66.76, cycle I increased to 73.82 in cycle II to 83.82. Initial classical completeness only reached 38.23%, in cycle I it increased to 67.64% and in cycle II to 94.11%.